From practice to lifestyle: conceptualizations of yoga in regular Ashtanga yoga practitioners using reflexive thematic analysis - Ramirez-Duran, Daniela; Kern, Margaret L.; Stokes, Helen (Frontiers in Psychology, 2025)
Yoga is usually defined and researched as a mind-body practice used for stress reduction, fitness and general health and wellbeing. While there are widely accepted definitions found in traditional texts and contemporary literature, as a millennial tradition yoga has evolved throughout time, places and people. Less is known about how regular yoga practitioners perceive, experience, and define yoga today. This study focused on a group of regular Ashtanga yoga practitioners (n = 200) to explore their conceptualizations of yoga in general, yoga philosophy, and their yoga practice using Reflexive Thematic Analysis. Yoga was defined as a practice for health and wellbeing, a method for personal inquiry and growth, a way of living, and a spiritual quest. Yoga philosophy was defined as the collection of ancient teachings for understanding human functioning and consciousness, providing a foundation for yoga practice and living life. Yoga practice was defined as the formal daily yoga ritual, adaptable, ever-changing, permeable and permeating into daily life. Three common threads revealed the entanglement of different elements and the significance of yoga as (1) an embodied integrated practice, (2) an embodied path for self-knowledge, and (3) a path for spiritual development. This entanglement and shared meanings underscore the relevance of considering participants' perspectives of yoga in research and applied settings to challenge assumptions and the prevailing image of yoga as mainly a physical and stress-reduction activity.